Adjunctive Immunotherapy With Polyclonal Ig-M Enriched Immunoglobulins for Septic Shock: From Bench to Bedside. The Rationale for a Personalized Treatment Protocol - Busani, Stefano; Roat, Erika; Tosi, Martina; Biagioni, Emanuela; Coloretti, Irene; Meschiari, Marianna; Gelmini, Roberta; Brugioni, Lucio; De Biasi, Sara; Girardis, Massimo (Frontiers in Medicine, 2021)
Septic shock still has a high mortality rate which has not hinted at decreasing in recent years. Unfortunately, randomized trials failed mainly because the septic patient was considered as a homogeneous entity. All this creates a sort of therapeutic impotence in everyday clinical practice in treating patients with septic shock. The need to customize therapy on each patient with sepsis has now become an established necessity. In this scenario, adjuvant therapies can help if interpreted as modulators of the immune system. Indeed, the host's immune response differs from patient to patient based on the virulence of the pathogen, comorbidity, infection site, and prolonged hospitalization. In this review, we summarize the rationale for using immunoglobulins as an adjunctive treatment. Furthermore, we would like to suggest a possible protocol to personalize treatment in the different clinical scenarios of the host's response to serious infectious events.